Analisis Penyebab Karyawan Resign pada Project Perusahaan BPO (Business Process Outsourcing): Studi PT. Transcosmos Indonesia Project Tokopedia Semarang - Andu, Christine Purnamasari (representamen, 2021)
The research aims to know (1) The caused of the employee resignation at outsourcing company (2) The majority reasons of those resignation. This researchused qualitativemethod with research locationSemarang City. Data used for this were primary and secondary data. Primary data or main data is taken from the informants itself, while secondary data or additional data are collected from many sources such as books, journal, company’s notes and other valid source to support this research completion. Total informants weretwenty eight, based on employee’s data for resignation periode January 2020 – December 2020 at PT Transcosmos Indonesia (Tokopedia Semarang Project). Data collection were done by interviewed with those twenty eightinformants, then being analysed by two theoriessuch as Social Judge Theory and Information Integration Theory. Research showed that there were four (4) main reasons employee submitting resignation such as : getting a new job, family issue, health issue, and wanting to be an entrepreneur. Keywords : Company, Outsourcing, Resignation